2018
DOI: 10.31742/ijgpb.78.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity computation in sesame genotypes using morphological traits and genic SSR markers

Abstract: Sesame (Sesamum indicum L.), the most ancient and important oilseed crop, with rich source of protein, highquality seed oil and many antioxidant properties is extensively grown in India. In the present study, 235 genic markers developed through data mining of expressed sequence tags from the NCBI database were used to assess the molecular genetic diversity at molecular level of 70 genotypes, belonging to different eco-geographical regions of the world. Of the developed markers, 35 (15%) showed polymorphism wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mean comparisons among treatment means were conducted by the Least Significant Difference (LSD) test at 5% levels of significance Estimation of genetic parameters: The phenotypic and genotypic coefficients of variation were estimated according to the following formula: Genotypic variance (δ 2 g): 2) indicated that days to 50% flowering, days to maturity, plant height (cm), branches per plant, capsules per plant, biomass yield per hectare (kg/ha), seed yield per hectare (kg/ha) and harvest index (%) were highly significant (p<0.01) among tested sesame genotypes except stem height which was no significant indicating that the presence of considerable variation in the genetic materials. In line with this result, the existence of considerable variation among tested sesame genotypes was reported by Abate et al 7 , Iqbal et al 9 and Singh et al 10 .…”
Section: Discussionsupporting
confidence: 79%
“…Mean comparisons among treatment means were conducted by the Least Significant Difference (LSD) test at 5% levels of significance Estimation of genetic parameters: The phenotypic and genotypic coefficients of variation were estimated according to the following formula: Genotypic variance (δ 2 g): 2) indicated that days to 50% flowering, days to maturity, plant height (cm), branches per plant, capsules per plant, biomass yield per hectare (kg/ha), seed yield per hectare (kg/ha) and harvest index (%) were highly significant (p<0.01) among tested sesame genotypes except stem height which was no significant indicating that the presence of considerable variation in the genetic materials. In line with this result, the existence of considerable variation among tested sesame genotypes was reported by Abate et al 7 , Iqbal et al 9 and Singh et al 10 .…”
Section: Discussionsupporting
confidence: 79%
“…It has been found that the average number of alleles per primer has the value of 5.85. This result was greater compared to SSR (3.42) and RAPD markers (3.45) [16,38] and lower than iPBSretrotransposon (8.83) and SRAP markers (9.96) [4,39]. The percentage of polymorphism varied from 33% for primer UBC812 to 100% for primers UBC810, UBC811 UBC815, UBC817, and UBC828.…”
Section: Pisum Genusmentioning
confidence: 82%
“…As the primary center of origin, Indian sesame cultivars have broad variability for different agro-morphological traits; nevertheless, there is limited information on the genetic diversity in Indian sesame. Developing a core set of sesame germplasm (generally 10% of an entire collection) is efficient for accessing available genetic diversity (Iqbal et al, 2018). However, a major limiting factor for productivity is the narrow genetic base with single genotypes subjected to mutation and selection to develop cultivars.…”
Section: Conservation Of Sesame Germplasm Worldwidementioning
confidence: 99%